Amalan pengajaran guru, masalah penguasaan kemahiran bahasa dan strategi pembelajaran bahasa dalam kalangan murid pemulihan khas - Roslan, Chin (2016)
Failure in mastering the basics of reading, writing and arithmetic (3M) skills among pupils in the primary school in this country is an on-going predicament. The gap between the achievement level of mastering the 3M skills of students in the mainstream and Special Remedial students is still significant. The failure of some teachers in implementing the Special Remedial Program has resulted in students lagging behind in learning. This study aims to explore teaching practices, analyse problems in mastering of the language skills and language learning strategies for the Malay Language subject among students of the Special Remedial Program. This qualitative study used exploratory case study design, explanation and description by using the embedded method. The study used the Al-Ghazali Teaching Model, Teacher Model as Determinants Assessment, Quality Appropriate Incentive Time (QAIT) Model, and the Language Learning Strategy Model by Ellis and Sinclair (1989). A total of six Special Remedial teachers from six schools in Perlis were selected purposively. Data were collected through observations, document analysis and interviews. Data were analyzed using constant comparative analysis. The results showed that research participants planned their lesson as stipulated in the Special Remedial syllabus. However, they decided to modify their teaching plans and activities according to the proficiency level of the students. Reading and writing skills were the main focus of the participants, while listening and speaking occurred indirectly and sometimes diregarded. This study also revealed that the problems of language proficiency varied between individuals among Special Remedial students. It also found that Visual Audio Kinesthetic Tactile (VAKT) language teaching and learning strategies, Chart Book Computer Fun (CBCF) and language tables were applied by the participants to overcome language proficiency problems among Special Remedial students. This study has contributed to Special Remedial education in acquisition of the Malay Language skills. The study also has implication on the quality of teaching and teacher professionalism with the use Special Remedial Teacher Teaching Model and Effective Remedial Teacher Teaching Model.